Pengaruh Penerapan Kombinasi Self Help Group dan Penggunaan Mobile Messaging Apps terhadap Kualitas Hidup Klien Gagal Ginjal Kronik di Ruang Hemodialisa RST dr. Reksodiwiryo Padang - Yanti Nopita; Susmiati Susmiati; Emil Huraini (FORIKES, 2020)
Hemodialysis is a kidney replacement therapy for clients with chronic renal failure. Hemodialysis therapy helps the client's survival, but on the other hand the client will experience various problems including psychosocial problems, which ultimately affect the client's quality of life. Self Help Group is a social support therapy and the Mobile Messaging Apps (WhatsApp) application can be used in Self Help Group. The purpose of this study was to determine the effect of implementing a combination of Self Help Group and the use of Mobile Messaging Apps on the quality of life of clients with chronic kidney failure. The research design was quasy experiment with pre and post test design with control group, the sampling technique was simple random sampling. The research sample consisted of 42 people, consisting of 21 respondents in the control group and 21 in the intervention group. The test results showed the effect of implementing a combination of Self Help Group and the use of Mobile Messaging Apps on the quality of life of clients with p value < 0.05. It is recommended that Self Help Group and the use of WhatsApp be implemented as part of nursing interventions in nursing care. Keywords: mobile messaging apps; quality of life; self help group ABSTRAK Hemodialisa merupakan salah satu terapi pengganti ginjal bagi klien gagal ginjal kronik. Terapi hemodialisa membantu kelangsungan hidup klien, namun di sisi lain klien akan mengalami berbagai masalah termasuk masalah psikososial, yang pada akhirnya mempengaruhi kualitas hidup klien. Self Help Group adalah salah satu terapi dukungan sosial dan aplikasi Mobile Messaging Apps (WhatsApp) aplikasi yang dapat digunakan dalam Self Help Group. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh penerapan kombinasi Self Help Group dan penggunaan Mobile Messaging Apps terhadap kualitas hidup klien gagal ginjal kronik. Desain penelitian yang digunakan yaitu quasy experiment dengan rancangan pre and post test with control group, teknik pengambilan sampel yaitu simple random sampling. Sampel penelitian berjumlah 42 orang terdiri dari 21 responden kelompok kontrol dan 21 kelompok intervensi. Hasil uji menunjukkan adanya pengaruh penerapan kombinasi Self Help Group dan penggunaan Mobile Messaging Apps terhadap kualitas hidup klien dengan p value < 0,05. Direkomendasikan Self Help Group dan penggunaan WhatsApp diterapkan sebagai bagian intervensi keperawatan dalam asuhan keperawatan. Kata kunci: mobile messaging apps; kualitas hidup; self help group